Access to homebuyer credit and housing satisfaction among households buying affordable apartments in urban Vietnam - Nguyen Tuan Anh; Tran Quang Tuyen; Vu Van Huong; Luu Quoc Dat (Cogent Economics & Finance, 2019)
This study examines the relationship between the access to homebuyer credits and housing satisfaction among those buying affordable apartments, using a sample of 1,000 respondents from our own survey in 2016 in Hanoi, Da Nang and Ho Chi Minh Cities. Our regression analysis reveals the education level, the size and value of apartments are closely linked with the access to preferential homebuyer credits. Notably, we find that the access to preferential home loans has a strongly positive impact on housing satisfaction, after controlling for all other factors in the model. Thus, the finding confirms that preferential home loan programs play an important role in helping low-income households own affordable apartments and increase their housing satisfation. We also find that some other features of their apartments, such as the number of bathrooms and balconies, the distance from the apartment building to schools, bus stations and markets, are strongly linked with housing satisfaction.
Keywords: D4; D6; D11; 330; affordable apartments; homebuyer credit; housing satisfaction; Vietnam